The first data about the hibernation of daubenton's bat (Myotis daubentonii) in the Paneriai tunnel (Vilnius, Lithuania) - Baranauskas, Kazimieras (2003)
Bat hibernation conditions as well as diversity and abundance of hibernating bats were investigated in the Paneriai tunnel (Vilnius, Lithuania) in 2000-2003. Five bat species were found to hibernate in the tunnel: Daubenton's bat (Myotis daubentonii), pond bat (Myotis dasycneme), brown long-eared bat (Plecotus auritus), barbastelle bat (Barbastella barbastellus), and serotine bat (Eptesicus serotinus). It was established that about 130 bats roost in the hibernation site every year, Daubenton's bats constituting 72% of them. That is the largest known hibernating cluster of Daubenton's bats in southeastern Lithuania. The Paneriat tunnel is protected as an engineering monument. It is recommended that the tunnel should be granted the status of a bat reserve.